2002
DOI: 10.1093/hmg/11.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function of axonemal dynein Mdnah5 causes primary ciliary dyskinesia and hydrocephalus

Abstract: Primary ciliary dyskinesia (PCD), also known as Kartagener's syndrome, is a human syndrome that results from ciliary dysfunction. This syndrome is characterized by recurrent respiratory infections, situs inversus and infertility. In some cases, hydrocephalus is also observed. We have characterized an insertional mutation in a mouse axonemal dynein heavy chain gene (Mdnah5) that reproduces most of the classical features of PCD, including recurrent respiratory infections, situs inversus and ciliary immotility. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
145
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 29 publications
12
145
0
1
Order By: Relevance
“…We have not only confirmed that the iv model has static respiratory cilia at 37 • C, but that it develops PCD-related disease including rhinitis, sinusitis, and otitis media. Consistent with other PCD mouse models [Ibanez-Tallon et al, 2002;Lee et al, 2008;Tanaka et al, 2004], none of the mice in this study developed significant lung pathology. This is perhaps an agerelated phenomenon (our oldest mice were 42 weeks old), or lack of disease may be associated with the relatively sterile environment of the animal facilities as suggested for CF models [Davidson and Rolfe, 2001].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We have not only confirmed that the iv model has static respiratory cilia at 37 • C, but that it develops PCD-related disease including rhinitis, sinusitis, and otitis media. Consistent with other PCD mouse models [Ibanez-Tallon et al, 2002;Lee et al, 2008;Tanaka et al, 2004], none of the mice in this study developed significant lung pathology. This is perhaps an agerelated phenomenon (our oldest mice were 42 weeks old), or lack of disease may be associated with the relatively sterile environment of the animal facilities as suggested for CF models [Davidson and Rolfe, 2001].…”
Section: Discussionsupporting
confidence: 90%
“…A significant proportion, including Dnahc5 (MIM# 603335) [Tan et al, 2007], Poll (MIM# 606343) [Kobayashi et al, 2002], and Dnaic1 (MIM# 604366) [Ostrowski et al, 2010], demonstrate additional defects, particularly hydrocephalus and cardiac anomalies, reducing their viability and raising significant animal welfare issues. The repeated demonstration that mutation of human PCD loci in the mouse results in hydrocephalus has led some to suggest an underlying difference in physiology [Ibanez-Tallon et al, 2002;Ostrowski et al, 2010]. The nm1054 mouse (MGI: Del(1)1Brk), a six-gene deletion, gives rise to PCD-like upper respiratory pathology, lacks cardiac defects, and only shows hydrocephalus on certain genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced movement of ciliary beating causes primary ciliary dyskinesia, including Kartagener syndrome, characterized by situs inversus, bronchiectasis, and chronic sinusitis (40). Such dysmotility or immotility of the cilia results from genetic mutations of major components of the axonema such as dyneins (52)(53)(54), DNA polymerase (55), sperm-associated antigen 6 (56), and a thioredoxin family member (57). In this study, we demonstrated that HSF1 is required for maintenance of ciliary beating in various organs such as the nasal cavity, ventricles, trachea, and oviducts.…”
Section: Discussionmentioning
confidence: 77%
“…These are genes coding for the dynein axonemal intermediate chain 1 (DNAI1) (8)(9)(10) and the dynein axonemal heavy chain 5 (DNAH5) (11). Loss of function of the murine Dnah5 dynein gene also causes PCD in the mouse (12). Other genes coding for axonemal dyneins, such as the heavy chain DNAH9, the intermediate chain DNAI2, and the light chain LC8, were recently excluded as major causes of PCD (13, 14, † †).…”
mentioning
confidence: 99%